Is There A Systemıc Inflammatory Effect of Cholesteatoma? - Kılıçkaya,M. Mustafa (2017)
Abstract Introduction Inflammation causes squamous epithelial transformation of the mucosa in the middle ear cavity and plays a role in the onset, growth, spread, and recurrence of cholesteatoma. Objectives The objective of this study is to investigate the systemic inflammatory effect in chronic otitis with cholesteatoma. Methods The study included a total of 311 patients comprising 156 patients with a pathology diagnosis of cholesteatoma and a control group of 155 with no active inflammation. The Neutrophil-to-lymphocyte Ratio (NLR) was calculated by dividing the neutrophil value by the lymphocyte value. Results The mean NLR was 1.94 ± 0.91 in the patients with cholesteatoma and 1.94 ± 0.85 in the control group. We determined no statistically significant difference between the groups in respect of NLR (p = 0.983). We calculated the NLR as 2.01 ± 1.00 in patients with ossicle erosion and 1.82 ± 0.69 in those without ossicle erosion, 1.86 ± 0.85 in patients with bone erosion and 1.98 ± 0.95 in those without bone erosion. We determined no statistical difference between these values (p = 0.175). Conclusion The results of this study showed that NLR had no predictive value in respect of bone erosions and associated complications in patients with cholesteatoma. The inflammatory effect of cholesteatoma is not systemic but remains more local.